The energy transition in France: Expansion of renewables stalling, good progress on heat pumps - Adeline Guéret; Wolf-Peter Schill (DIW Weekly Report, 2024)
The energy transition is a major challenge for both Germany and France. This Weekly Report provides an overview of the short- and long-term goals as well as current developments and trends in France's energy and climate policy. It reveals that France is largely on track with its greenhouse gases targets and is also making good progress on installing heat pumps. However, its expansion of renewable energy capacities is falling short. Differences in the energy policies of France and Germany are most apparent in the power sector: While France is prioritizing nuclear power, Germany is relying heavily on renewable energy. For France to achieve its climate goals, it will have to expand renewable energy faster. One challenge faced by both countries is their planned electrification of mobility and space heating.
Keywords: Q40; Q42; Q48; 330; France; energy policy; energy transition